Variation in cardiovascular magnetic resonance myocardial contouring: Insights from an international survey. Issue 4 (17th February 2019) - Moody, William E.; Hudsmith, Lucy E.; Holloway, Ben; Treibel, Thomas A.; Davies, Rhodri; Kozor, Rebecca; Hamilton‐Craig, Christian; Edwards, Nicola C.; Bradlow, William M.; Moon, James C.; Steeds, Richard P.; ,
Abstract : Level of Evidence: 5 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2019;50:1336–1338.